Socioeconomic status. The relationship with health and autoimmune diseases (2014)
Socioeconomic status (SES) is a hierarchical social classification associated with different outcomes in health and disease. The most important factors influencing SES are income, educational level, occupational class, social class, and ancestry. These factors are closely related to each other as they present certain dependent interactions. Since there is a need to improve the understanding of the concept of SES and the ways it affects health and disease, we review herein the tools currently available to evaluate SES and its relationship with health and autoimmune diseases. © 2014 Elsevier B.V.